SISTEM KONTROL ROLLING DOOR MENGGUNAKAN SMARTPHONE BERBASIS ANDROID OS PADA PT. INDONESIA STANLEY ELECTRIC - Ferry Sudarto; Jahwahir Jahwahir; Ryan Satria (CCIT Journal, 2015)
PT Indonesia Stanley Electric is a company founded to meet the needs of vehicle lighting equipment 2 wheel and 4 wheel PT ISE start molding and light industry preferred the lighting equipment of motor vehicles, and the next stage is planning the manufacture of electronic komponoen motor vehicle. Stanley company headquartered in Japan until now PT ISE has 34 branch companies in several countries outside of Japan. Stanley Company in Indonesia is a subsidiary branch to 24, which is named PT Indonesia Stanley Electric (PT ISE). PT Indonesia Stanley Electric is located at Jl. BhumiMas 1 No. Cikupamas Industrial Area 17, where the company is using the Rolling Door as a means of exit and entry of Forklift who still use manual systems and for operation by pressing the open or close button made by a another operator to operate Rolling Door. Smartphones with Android operating system more widely available in the market at a more affordable price. Android operating system itself is open source operating system that can be modified according to user needs. The control system uses the Android-based smartphone is used to control the Rolling Door from a certain distance without having to interact directly with the Rolling Door. In this study, a prototype device Rolling Door control system automatically uses the Android-based Smartphone controls associated with the program of the microcontroller ATMega8 implanted using the Bluetooth network. In a mechanical system that is functioning there is a DC motor to drive the Rolling Door, the system switches to use proximity switches to determine the stopping point of the system. For electronic systems use 12 volt dc relay circuit, and using bluetooth module HC-05. With this system the user can operate the tool to open and close the Rolling Door via Smartphone, in addition to be used as a means of communication but also used as a device that is communicated to control a hardware device.